Socioeconomic Determinants of Domestic Violence in Northeast India: Evidence From the National Family Health Survey (NFHS-4) - Haobijam, Sharatchandra (Journal of interpersonal violence, 2022)
Violence against women is now widely recognized as an important public health problem, owing to its health consequences. Domestic violence generally refers to violence against women that generally takes place in the matrimonial home, which includes physical, emotional, sexual as well as economical violence occurring in the adult relationship. Domestic violence has negative impact on the demographic outcome of a country or region, which includes the health and health seeking behavior of women. The present study is an attempt to investigate the socioeconomic factors that would significantly influence domestic violence in the northeastern region of India. The northeastern region of India comprises of eight states, including Manipur and Sikkim, which are reported having the highest and the least prevalence of domestic violence in the whole country according to NFHS-4. Considering these reports and having a different socioeconomic setup as compared to other states in the mainland India, we selected the region for the current study. Data from NFHS-4 conducted during 2015?16 is being employed for the present study. Findings show that education of women, wealth, women?s working status, religion, parity of women, and husband?s alcohol use are some of the significant covariates that might have influenced domestic violence. The overall prevalence of physical, emotional, sexual, and severe physical violence among women of northeastern India are 24.7%, 11.8%, 6.4%, and 5.3%, respectively. Logistic regression analysis computes the relative risks of categorical variables via the odds ratios. Those women who got higher education and are in upper wealth quintiles have less risk of experiencing domestic violence as compared to women in lower education and lower wealth quintile in northeastern India. There is no rural urban difference in experiencing domestic violence in the region.